Identification and clinical relevance of naturally occurring human CD8+HLA-DR+ regulatory T cells - Arruvito, Maria Lourdes (2014)
The lack of responsiveness to self and non-self Ags is normally maintained by multiple mechanisms, including the suppressive activities of several T cell subsets. In this study, we show that CD8+ T cells from both adult peripheral blood and umbilical cord blood mononuclear cells constitutively expressing HLA-DR represent a natural human CD8+ regulatory T cell subset. Their suppressive effect appears to be cell-to-cell contact dependent and may involve CTLA-4 signaling between neighboring T cells. These regulatory T cells can be expanded in vitro and exhibit a suppressive capacity similar to that observed in ex vivo CD8+HLA-DR+ T cells. The high frequency of CD8+HLA-DR+ T cells that we detected in patients with non–small cell lung cancer deserves further work to confirm their putative suppressor effect within the tumor.